HANDBOOK OF PSYCHOLOGICAL & SOCIAL INSTRUMENTS - PAREEK, UDAI; RAO, T.VENKATESWARA (VISHNUPRASAD PANDYA,SAHITYA MUDRANALAY, AHMEDABAD 380022, 1974)
Several research instruments have been developed and standardized in India, but these have not been widely publicized. As a result , these instruments are not fully utilized. In the absence of information about instruments developed in a particular area, unnecessary efforts have been duplicated to develop instruments, instead of building on the fulfil this important need..
Keywords: Psychological Testing